Transported to Botany Bay : Class, National Identity, and the Literary Figure of the Australian Convict - Elliott, Dorice Williams, 1951- (Book collections on Project MUSE., 2019)
"Literary representations of British convicts exiled to Australia were the most likely way that the typical English reader would learn about the new colonies there. In Transported to Botany Bay, Dorice Williams Elliott examines how writers--from canonical ones such as Dickens and Trollope to others who were themselves convicts--used the figure of the felon exiled to Australia to construct class, race, and national identity as intertwined. Even as England's supposedly ancient social structure was preserved and venerated as the 'true' England, the transportation of some 168,000 convicts facilitated the birth of a new nation with more fluid class relations for those who didn't fit into the prevailing national image. In analyzing novels, broadsides, and first-person accounts, Elliott demonstrates how Britain linked class, race, and national identity at a key historical moment when it was still negotiating its relationship with its empire. The events and incidents depicted as taking place literally on the other side of the world, she argues, deeply affected people's sense of their place in their own society, with transnational implications that are still relevant today"--